2021
DOI: 10.2147/ccide.s302770
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Attachment Adhesion to Ceramic Surfaces

Abstract: Ceramic materials are constantly evolving, achieving good functionality and aesthetics. Bonding to ceramics may be difficult because of high toxicity procedures and risk of surface damage. The review aims to answer several research questions: Is there a golden standard for bonding to ceramic? Are there adhesives or types of photopolymerization lamps that produce a higher bond strength on certain types of ceramics rather than others? Articles focusing on the bonding process of orthodontic attachments to ceramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Since ceramics are now used frequently in prosthodontics to meet patient aesthetic demands, orthodontists must choose proper methods of bonding to these materials to achieve optimum outcomes [26]. Ceramic materials are versatile and continuously evolving, making it possible to achieve the desired aesthetic results.…”
Section: Discussionmentioning
confidence: 99%
“…Since ceramics are now used frequently in prosthodontics to meet patient aesthetic demands, orthodontists must choose proper methods of bonding to these materials to achieve optimum outcomes [26]. Ceramic materials are versatile and continuously evolving, making it possible to achieve the desired aesthetic results.…”
Section: Discussionmentioning
confidence: 99%
“…The application of 9.6% HFA etching for 60 s was recommended for orthodontic attachment adhesion to ceramic surfaces in a recent review. 25 Asiry et al 26 reported that conventional pretreatment produced higher SBS values for LD ceramics than self-etching primer. This difference could be due to the acid remnants in the deep porosities of the non-neutralized ceramic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Therefore, it was necessary to assess the ceramic surfaces after detachment because of the risk of surface damage with or without remnant adhesives caused by high bond strength. 25 In this case, the RARI was developed and used for evaluation and scoring.…”
Section: Discussionmentioning
confidence: 99%
“…In general, in the present study SBS values were remarkably high (median: 33.6 MPa). This might be explained by the fact that ceramic brackets were bonded to ceramic surfaces [ 59 ]. Al-Hity et al found significant higher tensile bond strength values for ceramic brackets bonded to glass ceramic in comparison to metal brackets [ 2 ].…”
Section: Discussionmentioning
confidence: 99%